Development of a novel modified bitumen with waste materials - Fernandes, Sara R. M. (2013)
Currently there is a growing concern to minimize/conserve the natural resources used in road paving, as well as, the recovery of waste materials. As such, many studies have emerged where these issues, or part of them, are discussed. Under this assumption, the study of new binders that reduce the amount of bitumen, by adding waste, is essential for the sustainable development of the road paving industry. The main goal of this work is the development of an alternative bituminous binder with competitive performance. Thus, it aims at studying the addition of waste motor oil, waste high density polyethylene (HDPE) and styrene-butadiene-styrene (SBS) polymers into a conventional bitumen, in order to obtain a binder partially derived from waste, and at the same time, reducing the amount of bitumen used in the mixtures. According to the results obtained, it was concluded that the introduction of waste motor oil and polymers in the bitumen improves some properties, in particular an increase on the softening point. With regards to its influence on the mixtures performance, it was concluded that although the mixtures presented a lower stiffness modulus, they showed greater resistance to permanent deformation and fatigue and lower water sensitivity than the conventional mixture.